Penundaan Pelaksanaan Hak Suami Istri Pasca Akad Dalam Kawing Soro’ Pada Masyarakat Bugis Wajo Perspektif Sosiologi Hukum Islam - Fitriyani, Fitriyani; Akram, Muhammad Rafi'i Ali; Arman, Arman (Al-Mizan (e-Journal), 2025)
Kawing soro’ is a customary marital practice of the Bugis community in Sajoanging District, Wajo Regency, in which the marriage contract is carried out prior to the traditional wedding reception. This arrangement results in a deliberate postponement of marital rights and obligations after the contract, including restrictions on cohabitation, sexual relations, and physical proximity until the customary ceremony is completed. This study aims to describe the pattern of deferred marital rights within the kawing soro’ tradition and to analyze it from an Islamic legal perspective. The research employs a qualitative field approach complemented by a Islamic law sociology framework. Data were collected through interviews with community leaders, religious figures, traditional practitioners, and married couples, as well as through library research. The data were analyzed descriptively and analytically by correlating empirical findings with Islamic legal principles.The findings indicate that the postponement of marital rights in kawing soro’ is not solely grounded in the concept of siri’ (family honor), but is also influenced by the widespread twin marriage myth, which holds that sexual relations before the traditional reception may bring misfortune, as well as by social-status considerations and economic readiness of the families involved. In Islamic law, however, once the marriage contract is valid, the couple attains full rights to cohabit and engage in lawful marital relations, without the obligation to wait for the reception. Thus, the practice of kawing soro’ is more strongly rooted in local custom and cultural belief than in Islamic jurisprudence. These findings illustrate a normative tension between adat and Sharia, highlighting the need for balanced cultural education so that customary values can coexist with Islamic legal principles, ensuring the fulfillment of marital rights as prescribed by the Sharia.